2016
DOI: 10.21767/2254-6081.100051
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Metronomic Capecitabine (Xeloda) for Treatment of Metastatic Gastrointestinal Cancer: A Clinical Study

Abstract: Background: Metastatic gastrointestinal cancer (GI-cancer) is often a chronic disease where the treatment intention often is palliative. For such patients, it is important to offer treatments that can prevent tumor progression without reducing quality of life more than necessary. Metronomic chemotherapy involves continuous administration of cytostatic drugs at low doses without longer drugfree intervals. Capecitabine (Xeloda) is a prodrug, given in a tablet formulation, that is selectively converted to 5-Fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In contrast, the concept of low-dose continuous (metronomic) chemotherapy has been developed over the past 15 years, as it minimizes treatment side effects while targeting the endothelial cells of the tumor vasculature, which are not allowed to recover. 12,13 This therapy has been explored as NAC in clinical studies of ovarian, cervical, and breast cancers, where tumor reduction was observed. [14][15][16] Novel administration strategies for CRC-with the intent of understanding the mechanistic effects of this approach, as well as to identify potential clinically viable (endoscopic) biomarkers of positive therapy response-require the use of in vivo, primary models of the disease.…”
mentioning
confidence: 99%
“…In contrast, the concept of low-dose continuous (metronomic) chemotherapy has been developed over the past 15 years, as it minimizes treatment side effects while targeting the endothelial cells of the tumor vasculature, which are not allowed to recover. 12,13 This therapy has been explored as NAC in clinical studies of ovarian, cervical, and breast cancers, where tumor reduction was observed. [14][15][16] Novel administration strategies for CRC-with the intent of understanding the mechanistic effects of this approach, as well as to identify potential clinically viable (endoscopic) biomarkers of positive therapy response-require the use of in vivo, primary models of the disease.…”
mentioning
confidence: 99%
“…The term “metronomic chemotherapy” was coined to describe chemotherapy that involves the use of lower but active doses of chemotherapeutic drugs without prolonged rest periods in between [14] . Early studies on metronomic chemotherapy (MET), showed that the targets of this type of treatment were the endothelial cells of the tumor, which could not recover due to the continuous delivery of the drugs 14 , 15 , which translated in an anti-angiogenic effect [16] .…”
Section: Introductionmentioning
confidence: 99%
“…There was an improvement in therapeutic regimens for advanced CRC in the last few decades. The low dose metronomic palliative chemotherapy in patients with advanced CRC after failure of standard chemotherapy led to a dramatic increase in efficacy, reduction of mortality rates, and improves survival in the form of control symptoms, and enhances or improves quality of life which is important issue in that group of patients [6,7].…”
Section: Introductionmentioning
confidence: 99%